APPLYING TRANSACTIONAL RESPONSE THEORY TO TEACHING LITERARY READING COMPREHENSION OF FAREWELL TO THE ROYAL PALACE IN GRADE 11 - Quoc Kha, Tran (HNUE Journal of Science: Journal of Educational Science, 2026)
Facilitating readers’ experiential responses is one of the approaches to teaching literary reading comprehension in schools. This paper aims to clarify the fundamental principles of Transactional Response Theory as articulated in the works of prominent scholars such as Louise M. Rosenblatt, Richard Beach, James D. Marshall, Robert E. Probst, and Judith A. Langer. On that basis, the study proposes orientations for applying Transactional Response Theory to teaching literary reading comprehension of Farewell to Cuu Trung Dai (excerpted from Vu Nhu To) by Nguyen Huy Tuong in Grade 11 according to a three-step process, including activating prior experience and preparing responses, engaging with the text, and developing experiential responses. The application of Transactional Response Theory in teaching the reading comprehension of tragic literary texts is expected to foster active readers and contributes to the development of learners’ qualities and competencies.